The Place of Play Toys and Digital Cultures - Lauwaert, Maaike (MediaMatters, 2009)
Increasingly, technology is at stake in toys, games and playing. With the immense popularity of computer games, questions concerning the role and function of technology in play have become more pressing. A key aspect of the increasing technologization and digitalization of both toys and play is the vagueness of borders between producers, consumers and players. In these so-called participatory cultures, players do not simply play with toys designed behind closed doors but become co-designers. This book takes a critical look at the advantages and disadvantages of participatory cultures and places the changing world of toys, games and playing in a historical context. Contrary to many New Media and computer game studies, this book takes the historical background of these phenomena into account by situating the changing world of play in the context of the social and cultural processes of commodification, domestication and urbanization from the 1850s to the present.